Design of an amorphous ZnWSe2 alloy-based counter electrode for highly efficient dye-sensitized solar cells - (:unkn) unknown (My University, 2023)
One of the biggest obstacles in the commercialization of dye-sensitized solar cells (DSSCs) is the use of the very expensive and rare platinum (Pt) catalytic material as a reference counter electrode (CE). Since finding new CE materials for replacing the state-of-the-art Pt is still challenging, the discovery of low-cost CE materials with superior catalytic activity is of paramount importance. Here, innovative and effective ZnWSe2 alloy CE materials in the amorphous structure are designed with different Zn ratios by the magnetron sputtering route and employed in DSSC applications to overcome the above-mentioned challenges of Pt CE. The formation of an amorphous phase with various Zn contents is further verified using theoretical calculations. Various electrochemical measurements such as cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), and Tafel demonstrate that the optimum ZnWSe2 (denoted as ZnWSe2-3) alloy-based CE material possesses superior electrocatalytic activity, electrochemical stability, and fast reaction kinetics for an iodide/triiodide (I−/I3−) redox pair. Thanks to its low charge transfer resistance, high electrical conductivity, and large surface area, the cell employing ZnWSe2-3 CE reaches a power conversion efficiency (PCE) of 8.27% with enhanced short circuit current density (Jsc) and fill factor (FF) parameters, which are higher than those of DSSCs based on Pt (7.56%), WSe2 (6.35%), and other ZnWSe2-based CEs (6.20 to 7.41%). In addition to its improved photovoltaic (PV) performance, the cell employing ZnWSe2-3 CE exhibits prolonged photostability under operational conditions. This facile and efficient approach provides a promising direction to fabricate high-efficiency and electrochemically stable DSSCs. We thus believe that our work could provide an effective alternative for the design of high-performance and low-cost CE materials for PV applications.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Malzeme Bilimi; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE; MATERIALS SCIENCE, MULTIDISCIPLINARY; Genel Malzeme Bilimi; Fizik Bilimleri; Malzeme Kimyası; General Materials Science; Physical Sciences; Materials Chemistry